Use of the rebound long jump index for devising effective takeoff techniques - Fujibayasi, N.; Sakaguchi, S.; Kariyama, Y.; Zushi, K. (Japan Journal of Physical Education, Health and Sport Sciences, 2014)
The present study was conducted to examine the most effective takeoff movement for the Rebound Long Jump Test (RLJ test) under high-speed conditions. This test is designed to evaluate the ability to perform the ballistic stretch-shortening cycle movement for unilateral horizontal jump events on the basis of the RLJ index (RLJ index (m/s)=Jumping distance (JD (m))/Contact time (CT (s)). Subjects jump from a 0.1-m-high step to the ground after an approach run (falling jump), followed by jumping without interruption for as far as possible (propulsive jump). Eleven male college track-and-field athletes performed the RLJ test, and the RLJ index was calculated. On the basis of the average value of the RLJ index, the athletes were assigned to an upper level group (RLJ index>mean value) or a lower level group (RLJ index<mean value), and the takeoff movement of upper level group was considered the effective takeoff movement. The results suggested that it was important to minimize the rotation angle of the body, and to use a faster rotation velocity. This was achieved by 1) increasing the movement distance and velocity in the direction of the forward movement of the swing leg in the air, 2) minimizing the rotation angle of the foot and shank segment, and increasing that of the thigh segment during the initial phase, and 3) accelerating the rotation angle of the thigh segment again and swinging the swing-leg forward and up during the latter phase. These results suggest that the RLJ test and RLJ index provide a measure of the takeoff movement technique in terms of pre-rotation moment, the mechanism of rotation of the lower limb segment, and the swing moment of the swing leg.